Analysis of single-mode optical fiber splicing loss in telecommunications network systems - Widia Damayanti; Haryana Mohd Hairi; Dedi Irawan (Science, Technology, and Communication Journal, 2026)
This paper investigates the impact of angular misalignment on splice loss across five distinct types of single-mode fiber (SMF), a critical factor in optical fiber network reliability. We regularly analyze splice loss at misalignment angles ranging from 0.1° to 1°, evaluating performance at both 1310 nm and 1550 nm wavelengths. Our findings consistently show that increasing angular misalignment directly causes a significant increase in coupling loss, with the SMF-28e+ showing the lowest susceptibility, recording losses of 0.7299 dB at 1310 nm and 0.672 dB at 1550 nm for a 1° angle. These detailed insights into the angular misalignment tolerance of various SMF types is crucial for enhancing the design and deployment of robust and efficient optical fiber networks, ultimately minimizing signal degradation and improving overall network performance.